Expression analysis of genes associated with sucrose accumulation in sugarcane (Saccharum spp. hybrids) varieties differing in content and time of peak sucrose storage. (2nd January 2015) - Chandra, A.; Verma, P. K.; Islam, M. N.; Grisham, M. P.; Jain, R.; Sharma, A.; Roopendra, K.; Singh, K.; Singh, P.; Verma, I.; Solomon, S.; Adams, W.
Abstract Sucrose synthesis/accumulation in sugarcane is a complex process involving many genes and regulatory sequences that control biochemical events in source–sink tissues. Among these, sucrose synthase (SuSy), sucrose phosphate synthase (SPS), soluble acid (SAI) and cell wall (CWI) invertases are important. Expression of these enzymes was compared in an early (CoJ64) and late (BO91) maturing sugarcane variety using end‐point and qRT‐PCR. Quantitative RT‐PCR at four crop stages revealed high CWI expression in upper internodes of CoJ64, which declined significantly in both top and bottom internodes with maturity. In BO91, CWI expression was high in top and bottom internodes and declined significantly only in top internodes as the crop matured. Overall, CWI expression was higher in CoJ64 than in BO91. During crop growth, there was no significant change in SPS expression in bottom internodes in CoJ64, whereas in BO91 it decreased significantly. Apart from a significant decrease in expression of SuSy in mature bottom internodes of BO91, there was no significant change. Similar SAI expression was observed with both end‐point and RT‐PCR, except for significantly increased expression in top internodes of CoJ64 with maturity. SAI, being a major sucrose hydrolysing enzyme, was also monitored with end‐point PCR expression in internode tissues of CoJ64 and BO91, with higher expression of SAI in BO91 at early crop stages. Enzyme inhibitors, e.g. manganese chloride (Mn++), significantly suppressed expression of SAI in both early‐ and late‐maturing varieties. Present findings enhance understanding of critical sucrose metabolic gene expression in sugarcane varieties differing in content and time of peak sucrose storage. Thus, through employing these genes, improvement of sugarcane sucrose content is possible.